"Everything has to be qualified": Reading as Misreading in John Banville and Paul de Man. Issue 5 (20th October 2018) - D'hoker, Elke
ABSTRACT: This article discusses the influence of Paul de Man's critical theories on John Banville's most recent trilogy— Eclipse, Shroud, and Ancient Light —which stages a de Man–like scholar with a hidden past. A first part traces structures of reading and misreading in the novels and identifies them as compulsively self-deconstructive gestures on the part of Banville's narrators. While this self-reflexivity testifies to their fundamental skepticism about language, truth, and identity, it is also a means of asserting control. The second part investigates whether the narratives, notwithstanding their supreme self-awareness, also possess de Manian blind spots. The characterization of the "mad" Cass Cleave in the three novels shows the dividing line between sanity and madness, between the male narrating subjects and their female "others, " to be that of a naive, hermeneutic reading versus an endlessly self-deconstructive post-hermeneutic reading. Hence, the narrators' supreme self-consciousness seems to require a—silent or mad—other, typically a woman, whose alternative way of reading Banville's protagonists both envy and disdain.